DEA Approaches: Variable and Model Selection for Bank’s Efficiency Measurement - Dr. Jasvir S. Sura; Kavita Sandhu; Dr. Anju Lather; Gourav (Innovative Research Thoughts, 2022)
Data Envelopment Analysis (DEA) is one of the most widely used tools for measuring efficiency, especially in the banking sector. However, one of the major issues that arise in front of the researchers or practitioners is the selection of input or output variables. Different DEA approaches are available based on literature review, which views banks from different perspectives; some view banking as an intermediate while others view it as a producer. The main motive of this paper is to provide insight into different approaches of DEA and the specification of variables as input or output variables based on it. The present study discussed five approaches: intermediate, production, asset, value-added, and user cost. Moreover, the study discusses different software for measuring DEA efficiency to provide information to novice researchers or practitioners.